Expression of Heparanase in uterosacral ligaments of women with or without uterine prolapse. (January 2020) - Ben-Zvi, Masha; Herman, Hadas Ganer; Schreiber, Letizia; Sagiv, Ron; Bar, Jacob; Condrea, Alexander; Ginath, Shimon
Abstract: Objective: Pelvic organ prolapse (POP) is a global health problem for which the pathophysiological mechanism remains unclear. The loss of extracellular matrix proteins is considered an important molecular basis for this pathology. Heparanase is a heparin sulfate degrading endoglycosidase that has an important role in various biological processes and is a key component of extracellular matrix. The aim of this study was to compare expression of Heparanase in connective tissue of uterosacral ligaments in women with or without uterine prolapse. Study design: Thirty-nine women who underwent hysterectomy for benign reasons were enrolled in the study. Twenty-three women with uterine prolapse (stage ≥3) who underwent vaginal hysterectomy (VH) - POP group, were compared to sixteen women without uterine prolapse who underwent abdominal hysterectomy (stage <2) - control group. Uterosacral ligaments (USL) biopsies were obtained from all uterine specimens near their origin. All tissue samples were analyzed by immunohistochemistry and tested for the presence of Heparanase using antiheparanse antibody 733. Results: Heparanse positive staining was more common in the connective tissue of uterosacral ligaments in women with uterine prolapse. Positive staining was seen in 17/23 (73.9 %) women with uterine prolapse compared to 4/16 (25 %) without uterine prolapse (p = 0.003). On multivariate logistic regression analysis, positive staining displayed a trend for an independent association with POP, after controlling for menopausal status and parity (OR 13.57, 95 %CI 0.82–224.4, p = 0.06). Conclusion: Heparanase expression is more common in the connective tissue of uterosacral ligaments in women with uterine prolapse compared to women with no prolapse.